The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1007/s10681-015-1501-5
|View full text |Cite
|
Sign up to set email alerts
|

QTL mapping for flowering time in different latitude in soybean

Abstract: Flowering represents the transition from the vegetative to reproductive phase and plays an important role in many agronomic traits. For soybean, a short day (SD) induced and photoperiod-sensitive plant, delaying flowering time under SD environments is very important and has been used by breeders to increase yields and enhance plant adaptabilities at lower latitudes. The purpose of this study was to identify quantitative trait loci (QTLs) associated with flowering time, especially QTLs underlying the long juven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 58 publications
0
30
0
Order By: Relevance
“…E1 , E2 , and E3 have large effects on flowering in a wide range of latitudes, whereas the allelic effect of E4 is rather limited to high latitudes (Yamada et al, 2012; Tsubokura et al, 2013, 2014; Xu et al, 2013; Lu et al, 2015). Among these four soybean genes, E1 has the most marked effect on time to flowering (McBlain et al, 1987; Upadhyay et al, 1994; Tsubokura et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…E1 , E2 , and E3 have large effects on flowering in a wide range of latitudes, whereas the allelic effect of E4 is rather limited to high latitudes (Yamada et al, 2012; Tsubokura et al, 2013, 2014; Xu et al, 2013; Lu et al, 2015). Among these four soybean genes, E1 has the most marked effect on time to flowering (McBlain et al, 1987; Upadhyay et al, 1994; Tsubokura et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the conserved roles of CO and COL genes across plant species in photoperiodic flowering, there is no report that any COL genes are involved in the genetic variation of flowering time in soybean. Among the 11 major genes for flowering that have been reported so far ( E1 – E9 and J , reviewed by Cao et al, 2017; E10 , Samanfar et al, 2017), four maturity genes, E1 to E4 , are the main contributors to soybean adaptation to a wide range of latitudes (Liu et al, 2011; Jia et al, 2014; Jiang et al, 2014; Langewisch et al, 2014; Tsubokura et al, 2014; Zhai et al, 2014; Lu et al, 2015; Kurasch et al, 2017; Li et al, 2017). The floral repressor E1 encodes a protein that contains a bipartite nuclear localization signal and a region distantly related to the B3 domain, and is a possible transcription factor that represses FT2a and FT5a expression (Xia et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…QTLs have been widely used to identify genes corresponding to flowering time in various legumes such as soybean (Liu & Abe, 2009;Lu et al, 2015;Yamanaka et al, 2001;D. Zhang et al, 2013), mungbean (Isemura et al, 2012;Kajonphol, Sangsiri, Somta, Toojinda, & Srinives, 2012), pigeonpea (Kumawat et al, 2012), chickpea (Gaur, Samineni, Tripathi, Varshney, & Gowda, 2015), and common bean (Blair, Iriarte, & Beebe, 2006;Chavarro & Blair, 2010;González et al, 2016;Tar'an, Michaels, & Pauls, 2002), enabling genomics-based breeding for adaptation traits.…”
Section: Molecular Markers and Whole-genome Resequencingmentioning
confidence: 99%
“…QTL mapping studies have also revealed the involvement of novel LJ genes, other than j and e6 , in delayed flowering under SD conditions [16, 22, 34]. Liu et al [16] identified QTLs for the variations of flowering time that segregated in different latitudinal environments in a cross between early and late flowering Korean soybean cultivars.…”
Section: Introductionmentioning
confidence: 99%
“…Of these, two QTLs located in Chr4 and 16 were responsible for the control of flowering under the SD conditions found at lower latitudes. Lu et al [22] reported that two maturity loci, E2 and E3 , and two novel QTLs located in Chr16 that were involved in the variations of flowering time that segregated under SD conditions in a cross between photoperiod-insensitive cultivar AGS292 and the Thai LJ cultivar K3. Furthermore, the QTL mapping in a cross between the LJ cultivars Paranagoiana and PI159925 revealed two QTLs that regulated flowering time under SD conditions, one corresponding to E6 / J , or a linked novel locus, and one located in Chr2 (D1b linkage group) [34].…”
Section: Introductionmentioning
confidence: 99%